Arbovirus Surveillance in Field-Collected Mosquitoes From Pernambuco-Brazil, During the Triple Dengue, Zika and Chikungunya Outbreak of 2015-2017 - Krokovsky, Larissa; Paiva, Marcelo H. S.; Guedes, Duschinka R. D.; Barbosa, Rosângela M. R.; de Oliveira, André L. S.; Anastácio, Daniela B.; Pontes, Claudenice Ramos; Ayres, Constância F. J. (Frontiers in Tropical Diseases, 2022)
The (re) emergence of arboviruses around the world is a public health concern once severe outbreaks are usually associated with these infections. The co-circulation of Dengue (DENV), Zika (ZIKV) and Chikungunya (CHIKV) viruses in the past few years has caused a unique epidemic situation in Brazil. The northeast region of the country was the most affected by clinical complications from such arboviruses’ infections, including neurological disorders caused by ZIKV. In this particular region, Aedes mosquitoes are the main vectors of DENV, ZIKV and CHIKV, with Culex quinquefasciatus also considered as a potential vector of ZIKV. Therefore, virological surveillance in mosquitoes contributes to understanding the epidemiological profile of these diseases. Here, we report the circulation of DENV, ZIKV and CHIKV in Aedes spp. and Cx. quinquefasciatus female mosquitoes collected in areas with a high arbovirus circulation in humans in the Metropolitan Region of Recife, Pernambuco, Brazil, during the triple-epidemics of 2015-17. All the field-caught mosquitoes were sent to the laboratory for arbovirus screening after RNA extraction and RT-PCR/RT-qPCR. A total of 6,227 females were evaluated and, as a result, DENV, ZIKV and CHIKV were identified in Ae. aegypti, Ae. taeniorhynchus and Cx. quinquefasciatus mosquito pools. In addition, DENV and ZIKV were isolated in C6/36 cells. In conclusion, it is important to highlight that arbovirus surveillance performed in mosquitoes from DENV-ZIKV-CHIKV hotspots areas can serve as an early-warning system to target vector control actions more efficiently in each studied area.